Description of a geographically variable elongate rock-dwelling cichlid (Cichliformes: Cichlidae) from Lake Malaŵi, Africa - Stauffer, Jay R.; Konings, Adrianus F. (Zootaxa, 2023)
The rock-dwelling cichlids from Lake Malaŵi, known as mbuna, comprise a diverse group of haplochromine fishes that are placed among 14 genera. Within the mbuna, Pseudotropheus is a polyphyletic genus, which has served as a catch-all for many of these fishes. Recently, many of the species-groups within Pseudotropheus have been elevated to separate genera. Herein, we describe an elongate form that was originally placed in the Pseudotropheus elongatus species group but is now described as a member of Metriaclima.